2018
DOI: 10.31349/revmexfis.64.368
|View full text |Cite
|
Sign up to set email alerts
|

Síntesis y caracterización electroquímica de recubrimientos de multicapas metal cerámico de W/WN, Ti/TiN y WTiN

Abstract: La corrosión causa grandes pérdidas y daños catastróficos en plantas industriales y en la infraestructura. Entre los métodos para reducirla se encuentran los recubrimientos. El uso de recubrimientos multicapa metal-cerámico es eficiente para disminuir la corrosión en aceros, es considerada una opción viable, ya que ofrecen diversas ventajas respecto a los recubrimientos de una capa: una de estas ventajas es que son depositadas con espesores relativamente altos y son capaces de disipar las tensiones residuales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Another factor, that has been reported, is the higher correlation directly COF versus roughness, thus, if the roughness increases, so do the COF, as well as, the generation of cracks on the top surface, promoting anti-slip agents to induce the increase of slide load and friction, [40,41]. In this case, morphological analysis of previous reported, the coating A and B have shown cracks with spheres domes sharp on the top surface; thus, it inducing increase COF [8].…”
Section: Pin On Disk Testmentioning
confidence: 96%
See 1 more Smart Citation
“…Another factor, that has been reported, is the higher correlation directly COF versus roughness, thus, if the roughness increases, so do the COF, as well as, the generation of cracks on the top surface, promoting anti-slip agents to induce the increase of slide load and friction, [40,41]. In this case, morphological analysis of previous reported, the coating A and B have shown cracks with spheres domes sharp on the top surface; thus, it inducing increase COF [8].…”
Section: Pin On Disk Testmentioning
confidence: 96%
“…Due to the absence of Nickel and Chrome alloys in steel, in contact with the polymeric matrix of Vinyl Chloride, the metal surface shows abrasive wear. One friction experiment carried out by [8], showed that below 60 • C, the slip between PVC and steel, the surface damage was negligible. However, as the temperature between the contact pair increases, wear is generated in PVC waste and steel particles 0.444 mg of mass.…”
Section: Introductionmentioning
confidence: 99%